Tyramide signal amplification coupled with multiple immunolabeling and RNAScope in situ hybridization in formaldehyde‐fixed paraffin‐embedded human fetal brain. Issue 1 (27th February 2022) - Alzu'bi, Ayman; Sankar, Niveditha; Crosier, Moira; Kerwin, Janet; Clowry, Gavin J.
Abstract: Several strategies have been recently introduced to improve the practicality of multiple immunolabeling and RNA in situ hybridization protocols. Tyramide signal amplification (TSA) is a powerful method used to improve the detection sensitivity of immunohistochemistry. RNAScope is a novel commercially available in situ hybridization assay for the detection of RNA expression. In this work, we describe the use of TSA and RNAScope in situ hybridization as extremely sensitive and specific methods for the evaluation of protein and RNA expression in formaldehyde‐fixed paraffin‐embedded human fetal brain sections. These two techniques, when properly optimized, were highly compatible with routine formaldehyde‐fixed paraffin‐embedded tissue that preserves the best morphological characteristics of delicate fetal brain samples, enabling an unparalleled ability to simultaneously visualize the expression of multiple protein and mRNA of genes that are sparsely expressed in the human fetal telencephalon. Abstract : RNAscope can be combined with immunofluorescence in precious human fetal brain sections to reveal information about localization of transcription factor expression. ZIC4 and PAX6 occupy separate domains across the forebrain, whereas ZIC4 and FOXP2 show clear co‐localization in the dorsal thalamus.